Dataset for H2, CH4 and organic compounds formation during experimental serpentinization. (3rd September 2020) - Huang, Fang; Barbier, Samuel; Tao, Renbiao; Hao, Jihua; Garcia del Real, Pablo; Peuble, Steve; Merdith, Andrew; Leichnig, Vladimir; Perrillat, Jean‐Philippe; Fontaine, Kathy; Fox, Peter; Andreani, Muriel; et al.
Abstract: Serpentinization refers to the alteration of ultramafic rocks that produces serpentines and secondary (hydr)oxides under hydrothermal conditions. Serpentinization can generate H2, which in turn can potentially reduce CO/CO2 and produce organic molecules via Fischer–Tropsch type (FTT) and Sabatier type reactions. Over the last two decades, serpentinization has been extensively studied in laboratories, mainly due to its potential applications in prebiotic chemistry, origin of life in extreme environments, development of carbon‐free energies and CO2 sequestration. However, the production of H2 and organics during experimental serpentinization is hugely variable from one publication to another. The experiments span over a large range of pressure and temperature conditions, and starting compositions of fluid and solid phases are also highly variable, which collectively adds up to more than a hundred variables and leads to controversial results. Therefore, it is extremely difficult to compare results between studies, explain their variability and identify key parameters controlling the reactions. To overcome these limitations, we collected and analysed 30 peer‐reviewed articles including over 100 experimental parameters and ca. 30 mineral and organic products, hence building up a database can be completed and implemented in future studies. We then extracted basic statistical information from this dataset and demonstrate how such a comprehensive dataset is essential to better interpret available data and discuss the key parameters controlling the effectiveness of H2, CH4 and other organics production during experimental serpentinization. This is essential to guide the design of future experiments. Abstract : We collected and analysed 30 peer‐reviewed articles reporting experimental production of H2 and/or CH4 plus other organics and built a dataset including 135 experimental parameters and about 30 final mineral and organic products, and performed basic statistical analysis on this dataset. We demonstrate how such a comprehensive dataset is essential to discuss the key parameters controlling the production of H2, CH4 and other organics during experimental serpentinization and guide the design of future experiments.